Current Transformers' Saturation Detection and Compensation Based on Instantaneous Flux Density Calculations. (1st October 2016) - Fallahi, A.; Ramezani, N.; Ahmadi, I.
Abstract : One of the major problems in power system protection is current transformers saturation and inability of protective relays to recognize and compensate it. In this paper an approach is presented to identify current transformer saturation based on instantaneous flux density calculation. Also the calculated magnetizing current is used to saturation compensation. In the proposed algorithm, the instantaneous flux density and magnetizing current are calculated using Jiles-Atherton method. Using knee point flux density, a criteria is proposed to identify saturation phenomena in the current transformer and finally using calculated instantaneous magnetizing current, secondary current distortion has been compensated. To evaluate efficiency of the proposed algorithm, various types of faults, residual flux, fault occurring angle, CT burdens and DC components have been tested and the results evidence that the proposed algorithm is more accurate and reliable as well as faster than other algorithms and its error is obviously less than them.